La responsabilidad transfronteriza por productos defectuosos en la Unión Europea - Palao Moreno, Guillermo (2015)
Liability for defective products meets a modern legal framework applicable to cases which have an international nature in the European Union. However, the new regulatory developments have not solved the existing coordination problems and offer an unjustified complexity, so there is a certain risk that the objectives pursued by the European legislator in this strategic sector for the EU internal market are not going to be fulfilled. The objective of this study is to analyze the solutions contained in Regulation (EC) 442001, relating to jurisdiction, the recognition and enforcement of judgments in civil and commercial matters and Regulation (EC) 8642007, concerning the law applicable to non-contractual obligations («Rome II»), aswell as their interrelationship with other conventional instruments.